Comparison Between Short Term Outcomes of Lichtenstein and Desarda Repair for Inguinal Hernia - Natasha Kanwal Mirza, Imran Ali, Zahid Rasheed, Muhammad Rizwan, Gul Naz, Fawad Hameed, Muhamamd Khurram Jameel (Pakistan Journal of Medical & Health Sciences, 2023)
Desarda repair for inguinal hernia repair came into being in 2001 and was an alternative to the Lichtenstein repair where mesh placement is necessary. The procedure is thought to be simple, reproducible and avoids the complications of a mesh and thus favorable for resource limited countries. Aim of the study was to compare short term outcomes of Lichtenstein versus Desarda repair for inguinal hernia in terms of mean post-operative pain and frequency of post-operative wound infection, scrotal edema and hematoma. Methodology: This RCT was conducted at Surgical Unit I, Fatima Jinnah Medical University, Lahore. Diagnosis of inguinal hernia was confirmed on clinical examination and per-operative findings. Two groups were formed with one undergoing Desarda repair and one Lichtenstein repair. Post-operative scrotal edema and hematoma formation, pain scores and wound infection were recorded and evaluated for both groups. Results: The overall incidence of scrotal edema was 5.0% (n=3) with 6.7% in Lichtenstein group and 3.3% in Desarda repair group. The overall incidence of hematoma formation was 0% (n=0), and the overall wound infection rate was also 0%. The overall mean for pain score for all study participants was 2.73 S.D 1.36. Mean pain score in Desarda repair was 2.13 S.D 1.30 and 3.33 S.D 1.15 for Lichtenstein group (p-value 0.001). Conclusion: Desarda repair is an economical repair especially for resource-limited countries and should be undertaken in place of a Lichtenstein repair where mesh cost and availability poses a problem. The Desarda repair has a better morbidity profile than the Lichtenstein repair and with more data generation may have a place to become the standard open inguinal hernia repair technique. Keywords: Desarda Repair; Lichtenstein Repair; Short-term outcomes